1999
DOI: 10.1086/307016
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent X‐Ray Emissions from Regions near or on the Pulsar Surface

Abstract: We present a model of X-ray emission from rotation-powered pulsars, which in general consist of one nonthermal component, two hard thermal components, and one soft thermal component. The nonthermal X-rays come from synchrotron radiation of eB pairs created in the strong magnetic Ðeld near the neutron star surface by curvature photons emitted by charged particles on their way from the outer gap to the neutron star surface. The Ðrst hard thermal X-ray component results from polar-cap heating by the return curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
110
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(124 citation statements)
references
References 51 publications
14
110
0
Order By: Relevance
“…The X-ray luminosities in Saito (1998) and Possenti et al (2002) also include the total emission due to the pulsars plus PWNe, given the limited spatial resolutions of ASCA, RXTE, and BeppoSAX. Cheng et al (2004) divided the total X-ray emission into pulsed and nonpulsed components, and found that the X-ray luminosity of the pulsed component follows L X;pul /Ė 1:2 , which agrees with the model prediction L X /Ė 1:15 by Cheng & Zhang (1999). For nonpulsed emission, they got L X;npul /Ė 1:4 , where they supposed that the nonpulsed component comes mainly from PWNe and that the contribution of the nonpulsed component from pulsars is negligible.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…The X-ray luminosities in Saito (1998) and Possenti et al (2002) also include the total emission due to the pulsars plus PWNe, given the limited spatial resolutions of ASCA, RXTE, and BeppoSAX. Cheng et al (2004) divided the total X-ray emission into pulsed and nonpulsed components, and found that the X-ray luminosity of the pulsed component follows L X;pul /Ė 1:2 , which agrees with the model prediction L X /Ė 1:15 by Cheng & Zhang (1999). For nonpulsed emission, they got L X;npul /Ė 1:4 , where they supposed that the nonpulsed component comes mainly from PWNe and that the contribution of the nonpulsed component from pulsars is negligible.…”
Section: Introductionsupporting
confidence: 68%
“…The nonpulsed component originates from the cooling of the neutron star, emitted from the whole pulsar surface with a characteristic temperature of about 0.1 keV, while the pulsed component comes from hot spots ($1.0 keV) on the pulsar surface, which are heated by the bombardment of relativistic particles streaming back to the surface from the pulsar magnetosphere (Kundt & Schaaf 1993;Zavlin et al 1995;Gil & Krawczyk 1996). The pulsar's nonthermal emission arises from the pulsar magnetosphere, and it might also contain pulsed (e.g., Cheng & Zhang 1999;Zhang & Harding 2000) and nonpulsed components (e.g., Tennant et al 2001;Becker et al 2004). In some cases, a pulsar wind nebula ( PWN ) is found to surround a RPP.…”
Section: Introductionmentioning
confidence: 99%
“…For the double BB model a plausible explanation could be that the observed X-ray radiation originates from a heated polar cap characterized by two different thermal components (Cheng & Zhang 1999). The derived hydrogen column densities (N H ) are in both cases much larger than the value used in previous X-ray studies.…”
Section: Discussionmentioning
confidence: 83%
“…However, a plausible explanation could be that the observed X-ray radiation originates from a heated polar cap characterized by two different thermal components (see e.g. Cheng & Zhang 1999). The simultaneous double BB fit to the ROSAT and ASCA data implies emission luminosities of L 1 = (1.56 ± 0.25) × 10 30 erg s −1 and L 2 = (1.47 ± 0.25) × 10 29 erg s −1 for T 1 and T 2 components, respectively.…”
Section: Spectral Analysismentioning
confidence: 99%
“…Becker & Trümper (1997), Cheng & Zhang (1998) and others showed that X-ray emission from rotationally powered pulsars can have thermal and non-thermal components. Thermal radiation is expected to arise from the heating of the polar caps by particles returning from the outer magnetosphere, or from the cooling neutron star surface in the case of pulsars (i.e.…”
Section: Introductionmentioning
confidence: 99%